The general theory of shares and distribution Of dividend in a company under the companies Act 1965: with special reference to its legality Under the islamic perspective - Muhammad Hafiz, Mohd Shukri; Bakri, Abdul Karim (International Journal of Liberal Arts and Social Science, 2014)
Under company law, a share is the interest of a shareholder in a company. By the same token, shares also reflect the interest of a shareholder in a mudharabah or musharakah contract under the Islamic laws. Presently, a company which has been registered under the Companies Act 1965 is often regarded as a conventional company as opposed to a syariah-compliant company. Nevertheless, it is possible to harmonize the provision in the Companies Act 1965 with Syariah principles in relation to shareholding issues. This article focuses on the rights attached to ordinary shares and preference shares under the Companies Act 1965 and the compatibility of such rules with the Syariah principles. The concern is also to determine the legality of basic principles in relation to the distribution of dividend to shareholders in the light of Islamic perspective.